Estudo de aproveitamento do resíduo do beneficiamento de caulim como matéria prima na produção de pozolanas para cimentos compostos e pozolânicos - LIMA, Jefferson Maia (Universidade Federal do Pará, 2011)
The use of residue in civil construction can to become a activity of extreme important and more frequent, mainly due to amount available with potential of recycling, possible reduction of environments impacts. The kaolin industries produces two type of residue. The residue contain clay mineral kaulinite show potentially of is to employ by pozzolanas at the construction civil industry. This research evaluates the technical viability to production of pozzolanas from mixtures in various percentagens of kaulinitic residue with limestone, wanting increase the reactivity. The contents of replacement of cement for pozzolanas is of 10%, 20%, 30%, 40%, 50% e 60% was studied. The cement employed was CP I S 32 and the pozolanas was made in the laboratory. The following tests in the experiment cements were carried out: specific gravity, specific surface area, water of normal consistency, setting time and compressive strength. Also, were carried out mineralogical tests in the pozolanas. The incorporation of pozzolanas allowed to mortar obtain compressive strengths more than it reference even though in high contents. Due to the pozzolanas show a considerable hydraulic characteristic this it occurred. It waits of residue burned becomes a higher pozzolana to employ at the civil construction, mainly along with cement, mortars and concretes in the substitution of burning clays from natural deposits despite necessity of adding tests for confirmation and complementation of effects was observed.